Menyiapkan wirausahawan muda: Implementasi pelatihan kewirausahaan dalam meningkatkan kesiapan kerja pada Siswa SMKS PGRI Sukodadi - Novi Darmayanti; Ana Fitriyatul Bilgies; Ali Muhajir; Nurul Fauziyah; Anjar Sulistyowati; Fitri Dwi Anggraeni (Penamas: Journal of Community Service, 2026)
The transformation of economic structures and the increasing competition in the labor market require Vocational High School (SMK) graduates to possess strong work readiness and entrepreneurial competencies. This community service program aimed to enhance students’ entrepreneurial literacy and work readiness through the implementation of the Project-Based Entrepreneurial Learning with Business Model Simulation (PBEL-BMS) method. The model integrates project-based learning, Business Model Canvas simulation, and product-oriented mentoring within five systematic stages. The participants were 36 students of SMKS PGRI Sukodadi enrolled in the Creative and Entrepreneurship Project (PKK) course. Evaluation was conducted using pre-test and post-test assessments of entrepreneurial literacy and a rubric-based evaluation of the Business Model Canvas. The results indicated a significant improvement in average literacy scores from 52.5 to 83.0 (an increase of 30.5%), with the greatest improvement in business model comprehension (37.1%). The average Business Model Canvas quality score reached 81.8%, categorized as good. Beyond cognitive gains, students’ confidence, collaboration, and structured thinking skills also improved. Therefore, the PBEL-BMS method proves effective in strengthening entrepreneurial literacy and comprehensively enhancing vocational students’ work readiness.